Evaluation of the Stunting Reduction Acceleration Program in Kijang Kota Urban Village, East Bintan District 2019-2023 - Irwandi, Jaka (PT FORMOSA CENDEKIA GLOBAL, 2024)
Reducing the number of stunting cases is currently one of the most important goals of the Indonesian government. This study aims to evaluate the accelerated stunting reduction program in reducing the prevalence of stunting in Kijang Kota Village, East Bintan District. This research uses descriptive qualitative methods, with data collection techniques of interviews, documentation, and observation with 11 (eleven) informants. The results of this study indicate that the input indicators have supported both human resources and technology, facilities and infrastructure are sufficient. Process indicators are not yet optimal in effectiveness and efficiency, it is not effective, there are still high numbers of stunting cases. Furthermore, the output indicator, KRS income has no effect in increasing income. As well as the outcomes indicator of the positive impact produced, providing growth and development of a healthy child's diet.